2016
DOI: 10.3389/fonc.2016.00016
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Epigenetics of Glioblastoma: Applications and Overall Incidence of IDH1 Mutation

Abstract: Glioblastoma is the most fatal brain cancer found in humans. Patients suffering from glioblastoma have a dismal prognosis, with a median survival of 15 months. The tumor may develop rapidly de novo in older patients or through progression from anaplastic astrocytomas in younger patients if glioblastoma is primary or secondary, respectively. During the past decade, significant advances have been made in the understanding of processes leading to glioblastoma, and several important genetic defects that appear to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 61 publications
0
38
0
Order By: Relevance
“…Asparagine has a much smaller van der Waals volume than arginine, although the ranked polarities of these two amino acids are similar. R132Q IDH1 plays an important role in driving chondrosarcomas and a small number of gliomas, and mouse mR132Q IDH1 generates D2HG about 20-fold more efficiently than human R132H IDH1 in vitro (39,45). This mutation has the most similar ranking in hydrophobicity as compared with WT, but a smaller van der Waals volume.…”
Section: Generation Of Idh1 Mutants Engineered To Explore Mechanisticmentioning
confidence: 98%
“…Asparagine has a much smaller van der Waals volume than arginine, although the ranked polarities of these two amino acids are similar. R132Q IDH1 plays an important role in driving chondrosarcomas and a small number of gliomas, and mouse mR132Q IDH1 generates D2HG about 20-fold more efficiently than human R132H IDH1 in vitro (39,45). This mutation has the most similar ranking in hydrophobicity as compared with WT, but a smaller van der Waals volume.…”
Section: Generation Of Idh1 Mutants Engineered To Explore Mechanisticmentioning
confidence: 98%
“…Mutation in isocitrate dehydrogenase 1/2(IDH1/2), one of the key cellular enzymes that facilitate the decarboxylation of isocitrate to 2α-ketoglutarate in normal cell, becomes altered by missense mutation at amino acid 132 in its active site, in which the arginine is replaced by histidine in glioma, resulting in the making of 2-hydroxygluterate (2-HG) oncometabolite in place of normal α-ketoglutarate (α-KG) that forms in oxidative decarboxylation process and interfering with the Jumonji class of demethylase and DNA hydroxylase which induces an array of changes including TeT2 hydroxylase-oriented DNA hypermethylation, histone demethylase-oriented histone tail methylation, collagen propyl 4 hydroxylase-oriented collagen hydroxylation and HIF prolyl 4 hydroxylase-mediated hypoxia-induced factor that ultimately induces a high level of angiogenic expression of veGF, making IDH1/2 one of the most prime markers in glioma with immense prognostic value [91][92][93] . All of these phenomena cater to the initiation and perpetuality of glioma and also render problems in its treatment.…”
Section: Cellular Alterations: Epigenetic Reprogrammingmentioning
confidence: 99%
“…[36][37][38] Since 2008, several studies have reported an increase in overall survival from 30 to 40 months in patients with GBMs or AAs with IDH1 mutation versus those without this mutation. 16,28,[39][40][41] This survival benefit was also identified in patients with grade II gliomas, showing an increase in OS of 7 years in patients with IDH1 mutation versus patients without this mutation. 39 The best prognosis was found in patients with IDH1/2 mutant and 1p/19q codeleted tumors, whereas patients with IDH1/2 wild-type gliomas and glioblastoma-like genomic alterations (loss on chromosome arm 10q and TERT promoter mutation) tended to have the worst outcome.…”
Section: Secondary Gbmsmentioning
confidence: 65%
“…12 In primary GBMs, the most frequent genetic alterations observed are loss of heterozygosity (LOH) at 10q (65% of cases), amplification or mutation of epidermal growth factor receptor (EGFR) (22-40%), amplification of platelet-derived growth factor receptor (PDGFR) (7%), tumor protein 53 (TP53) mutation (28-31%), cyclin-dependent kinase inhibitor 2 A/B (CDKN2A/B) deletion (31%), phosphatase and tensin homolog (PTEN) mutation or deletion (24-30%), IDH1/2 mutation (5%), telomerase reverse transcriptase (TERT) promoter (10%), O6-methylguanine-DNA methyltransferase (MGMT) promoter methylation (36%), loss of expression of the retinoblastoma gene (RB1) (2%), phosphatidylinositol-4,5-bisphosphate 3-kinase A (PIK3CA) (1%), murine double minute 2 (MDM2) (7-12%), neurofibromatosis type 1 (NF1) deletion or mutations (11%), and glioma-associated oncogene homolog 1 (GLI1) (5-22%). 8,[13][14][15][16][17][18][19][20][21] In secondary GBMs, the most frequent genetic alteration observed are TP53 mutation (65% of cases), LOH at 22q (70-80%), LOH 19q (40-50%), IDH1/2 mutation (45-50%), MGMT promoter methylation (75%), CDKN2A/B deletion, PDGFR gene amplification (7%) 1p/19q codeletion (15-20%), and EGFR (5-7%). 16,17,20,[22][23][24][25][26]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation